Descripción de ocho especies nuevas de Photinus (Coleóptera: Lampyridae, Photinini) de México - Zaragoza Caballero, Santiago (Instituto de Ecología, A.C., 1995)
Eighit new species of Lampyridae are here in described, compared and illustrated viz.: Ph. parvusater sp. nov.; Ph. intermedius sp. nov.; Ph. dugesi sp. nov.; Ph. platyphallos sp. nov.; Ph. gorhami sp. nov.; Ph. mcdermotti sp. nov.; Ph. greeni sp. nov. y Ph. chihuahuensis sp. nov. The taxonomic status of Photinus ater (Duges) Gorham is commented and the altitudinal and latitudinal range of the nine species are given.